Satire and Contradiction in George Orwell’s Animal Farm: A Stylistic and Semiotic Study - Burmansyah Burmansyah; Komala Dwi Syaputr (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2025)
This research aimed to analyze figurative language in sentences in the novel Animal Farm. The primary object is Satire and Contradiction, and the secondary object to complement this study is Character. The purpose of this research is to find out what Figurative Language is found in sentences so that the hidden meaning in the sentence can be dissected. The researcher uses a descriptive qualitative method, with adopted two techniques in the theory of Molina and Albir (2002) on the translation of satire meaning and Nina Noorgard (2011) on multimodal stylistics – the happy marriage of stylistics and semiotics, linguistic compression techniques are used in answered the first research question, and semiotic analysis is used to answer the second research question. The researcher found 35 sentences contain irony, metaphor, simile, cynicism, sarcasm, hyperbole with a percentage of 52%, 26 sentences contain litotes, paradox, occupation, oxymoron, antithesis, histeron proteron with a percentage of 38%, and 7 sentences contain personality and habitude, with a percentage of 10%. Key Word: Satire, Contradiction, Character.